XML and Fuzzy-Based Two Various Knowledge Retrieval Methods in Edaphology - Meenakshi, Anantaraman; Mohan, Vasudev (Computing and Informatics, 2015)
In this paper, we propose a proficient method for knowledge retrieval in edaphology to assist the edaphologists and those who are related with agriculture in a big way. The proposed method mainly consists of two phases of which the first one is to build the knowledge base using XML and the latter part deals with information retrieval using fuzzy search. Initially, the relational database is converted to XML database. This paper discusses two algorithms, one is when the soil characteristics are given as input to have the plant list and in the other, plant names are given as input to have the soil characteristics suited for the plant. While retrieving the query result, the crisp numerical values are converted to fuzzy value using the triangular fuzzy membership function and matched to those in database. Those which satisfy are added to the result list and subsequently, the frequency is found out to rank the result list so as to obtain the final sorted list. Performances metrics are used in order to evaluate the method and compared to baseline paper to identify the number of plants retrieved, ranking efficiency, and computation time and memory usage. Results obtained proved the validity of the method and the method obtained the average computation time of 0.102 seconds and average memory usage of 2 486 Kb, which are all far better than our previous method results.